2002
DOI: 10.1088/0022-3727/35/23/309
|View full text |Cite
|
Sign up to set email alerts
|

Growth of self-assembled PbSe quantum-dots on GaSb(100) by liquid phase epitaxy

Abstract: Self-assembled PbSe quantum-dots (QD) have been grown on GaSb(100) substrates from the liquid phase. A Pb-rich melt at 517°C was used with 10°C supercooling and with a short (10 ms) melt-substrate contact time. Atomic force microscopy has revealed that the PbSe QDs are 4–10 nm in height and 10–40 nm in diameter, with an area density of 1.7×1010 cm−2. The growth of QDs occurs in the Volmer–Weber mode and is a result of the difference in lattice structures between the PbSe and GaSb rather than the lattice consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In agreement with the AFM and RHEED observations, a highly isotropic 3D QD-shape with (1 1 1)-oriented PbTe facets was clearly observed. No wetting layer at the heterointerface is a characteristic of the lattice-type mismatched epitaxy [8,9]. For the QW sample, on the other hand, the HRTEM observation revealed a coherent PbTe lateral growth to the CdTe buffer layer without introducing dislocations.…”
Section: Resultsmentioning
confidence: 97%
“…In agreement with the AFM and RHEED observations, a highly isotropic 3D QD-shape with (1 1 1)-oriented PbTe facets was clearly observed. No wetting layer at the heterointerface is a characteristic of the lattice-type mismatched epitaxy [8,9]. For the QW sample, on the other hand, the HRTEM observation revealed a coherent PbTe lateral growth to the CdTe buffer layer without introducing dislocations.…”
Section: Resultsmentioning
confidence: 97%
“…The self-organization of PbSe and PbS islands by latticemismatch epitaxy on III-V substrates has already been demonstrated [23,24]. A reason to choose one of these two families would be to avoid the use of Te, which is scarce.…”
Section: The Lead Salt Qd Materials Systemsmentioning
confidence: 99%
“…Specifically, midinfrared light emitters and detectors based on narrow-gap IV-VI materials could benefit significantly from high-quality nearly lattice-matched III-V substrates, as native IV-VI substrates are fragile, poor dissipaters of heat, * kunalm@ucsb.edu and limited in quality and availability. To this end, we note that PbSe/GaSb heterostructures have been proposed [20] for mid-IR lasers, although only one study [21] on PbSe/GaSb growth has been reported, the latter using liquid phase epitaxy (LPE) to synthesize PbSe quantum dots on GaSb. Controlling the atypical heterovalent interface atomic arrangement between these materials will also grant control over the induced interfacial charge, with both electronic and structural implications for thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This disorder creates significant interfacial energy penalties for epitaxy and diminishes the possibility for layer-by-layer growth. As a majority of the work on IV-VI semiconductors has utilized fluorite substrates or buffers of CaF 2 and BaF 2 , literature on the early stages of growth of IV-VI materials on III-V substrates is limited [21,[25][26][27]. On (001) GaAs, PbTe has been observed to grow in mixtures of (001) and (111) orientations [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation